Correction: An investig-ation into the epidemiology of chikungunya virus across neglected regions of Indonesia. - PLOS Neglected Tropical Diseases Staff (Public Library of Science (PLoS), 2022)
[This corrects the article DOI: 10.1371/journal.pntd.0008934.].